A STREETCAR NAMED DESIRE : STUDY IN ABSURDISM - K. Singh, Dr Bimlesh (Innovative Research Thoughts, 2017)
Tennessee Williams’ plays depict the pathos of human failure in modern age. He has concentrated on the inner/the psychological lives of characters impinged by harsher reality. The characters (Amanda, Blanche etc.) emerge as victims of absurd outward pressures of brutal social realism thereby disillusioning them and shattering them to piers. The decadence of the Southern myth and its pristine glory rightly subjects its creatures to crushing discomfiture. Robbed of ideal world of illusion, the characters abide a complacent seclusion which leads them to neurosis, frustration etc. Hence Williams’ play end on the irremediable plight of creatures of a moribund culture which had, to quote Margaret Mitchell, gone with the wind of the Northern invasion.